2021
DOI: 10.1111/ejh.13703
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐related adverse events in cancer patients being treated with immune checkpoint inhibitors

Abstract: Introduction:With the increased use of immune checkpoint inhibitors (ICI), it is essential to improve our understanding of immune-related adverse events (irAE). To date, most studies describing irAE have been performed in clinical trial populations, which may not be an accurate description of irAE in real-world populations. Also, identification of patients at increased risk of irAE is needed as early recognition may improve irAE outcomes.How to cite this article: Byrne MM, Lucas M, Pai L, Breeze J, Parsons SK.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition to common rashes and itchiness, RCCEP was one of the most common adverse drug reactions associated with camrelizumab. 25 , 26 In the Phase 2 clinical study of carrelizumab monotherapy for advanced HCC, 16 the incidence of RCCEP was 66.8% (145/217), respectively, and all events were grade 1 or 2, which did not lead to the interruption of treatment. It was observed that the incidence of RCCEP was significantly associated with higher objective response rate and prolongation of PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to common rashes and itchiness, RCCEP was one of the most common adverse drug reactions associated with camrelizumab. 25 , 26 In the Phase 2 clinical study of carrelizumab monotherapy for advanced HCC, 16 the incidence of RCCEP was 66.8% (145/217), respectively, and all events were grade 1 or 2, which did not lead to the interruption of treatment. It was observed that the incidence of RCCEP was significantly associated with higher objective response rate and prolongation of PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on pre-existing neurological conditions only, so the safety of ICI use in systemic inflammatory conditions is beyond the scope of our study [25]. We also did not adjust for other factors such as smoking, which may have been relevant, given that nearly half of our patients had lung cancer and smoking had been suggested as a possible predictor for development of irAEs [26,27].…”
Section: Limitationsmentioning
confidence: 99%